Study of volumes and content of material incentives of trade enterprise staff work - Шостак, Інна Володимирівна (Technology audit and production reserves, 2015)
Ongoing in our country political and economic reforms can’t be realized without the active creation of incentives to work and entrepreneurship in combination with highly organization and discipline. Recently, it is occurred the trend to increasing an interest and attention to the problems of staff incentives, and analysis of the prospects of employment activity because the assessment of the situation in the workplace is a necessary condition for the proper choice of direction and methods of implementation of measures for economic recovery. However, there is a crisis of labor activity in large part due to the loss of salary of its main functions: motivation and reproduction. These and other factors determine the relevance and importance of the problems of material incentives for work efficiency. The study of this issue in the trade becomes more important because the trade finishes the reproduction process or eliminates or increases difficulties that occurring in manufacturing. The features of the current state of staff stimulation in commercial enterprises are mixed hourly-wage premium form with elements of the commission; bonuses and allowances to employees; using different compensated programs, charging premiums for performing and overfulfillment of planned indicators of realization. It is conducted multivariate cluster analysis and the influence of the main factors on incentives for staff in commercial enterprises revealed that a third cluster of enterprises (enterprises with foreign investment) and a high level of increase of the basic salary (50 %). The increase in additional salary relatively basic (26 %) is typical for the second cluster (average trading companies). Increase of other incentive and compensation payments is typical for the first cluster (to 18-20).